2014
DOI: 10.1159/000362916
|View full text |Cite
|
Sign up to set email alerts
|

Vocal Behavior and Vocal Central Pattern Generator Organization Diverge among Toadfishes

Abstract: Among fishes, acoustic communication is best studied in toadfishes, a single order and family that includes species commonly known as toadfish and midshipman. However, there is a lack of comparative anatomical and physiological studies, making it difficult to identify both shared and derived mechanisms of vocalization among toadfishes. Here, vocal nerve labeling and intracellular in vivo recording and staining delineated the hindbrain vocal network of the Gulf toadfish Opsanus beta. Dextran-biotin labeling of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 65 publications
4
29
0
Order By: Relevance
“…A VMN dedicated to sonic functions has been experimentally demonstrated in 22 species following the labeling of one or more vocal nerve roots with either horseradish peroxidase or a biotin derivative (neurobiotin, biocytin, dextran-biotin) (Table 2.1). Intracellular recording and staining further verifies the position of VMN in three species of Batrachoidiformes (plainfin midshipman; oyster toadfish; and Gulf toadfish, O. beta) and one species of Perciformes (northern sea robin, Prionotus carolinus) (Pappas and Bennett 1966;Bass andBaker 1990, 1991;Chagnaud et al 2012;Chagnaud and Bass 2014). As listed in Table 2.1, VMN is positioned along the rostral-caudal axis in the caudal hindbrain medulla and/or the rostral spinal cord in all species so far investigated.…”
Section: Vocal Nerves and Vocal Motor Nucleusmentioning
confidence: 80%
See 2 more Smart Citations
“…A VMN dedicated to sonic functions has been experimentally demonstrated in 22 species following the labeling of one or more vocal nerve roots with either horseradish peroxidase or a biotin derivative (neurobiotin, biocytin, dextran-biotin) (Table 2.1). Intracellular recording and staining further verifies the position of VMN in three species of Batrachoidiformes (plainfin midshipman; oyster toadfish; and Gulf toadfish, O. beta) and one species of Perciformes (northern sea robin, Prionotus carolinus) (Pappas and Bennett 1966;Bass andBaker 1990, 1991;Chagnaud et al 2012;Chagnaud and Bass 2014). As listed in Table 2.1, VMN is positioned along the rostral-caudal axis in the caudal hindbrain medulla and/or the rostral spinal cord in all species so far investigated.…”
Section: Vocal Nerves and Vocal Motor Nucleusmentioning
confidence: 80%
“…The model was largely verified in midshipman fish by Bass and colleagues who provided the essential cellular level experiments (Bass and Baker 1990;Goodson and Bass 2000a;Kittelberger et al 2006). As recently shown by Chagnaud and colleagues (Chagnaud et al 2011Chagnaud and Bass 2014), the VPP and vocal pacemaker nuclei (VPN) discussed earlier code for call duration and fundamental frequency/PRR, respectively. VPP neurons receive PAG input (Kittelberger and Bass 2013) and project to the VPN-VMN region (Chagnaud et al 2011), acting as a link that gates forebrain/midbrain activation of hindbrain vocal sites (Kittelberger et al 2006).…”
Section: Anatomically Distinct Brain Nuclei Code For Vocal Charactersmentioning
confidence: 82%
See 1 more Smart Citation
“…Label was also robust in two ventral telencephalic nuclei, i.e., Vd and Vs, that have been compared, in part, to basal ganglia (Vd) and subpallial amygdala (Vs) of tetrapods [Mueller et al, 2008;Maximino et al, 2013], as well as in the preoptic area. Though label was not found in the neuronal populations comprising the hindbrain vocal CPG (VMN, VPP, and VPN) [Bass and Baker, 1990;Chagnaud et al, 2011Chagnaud et al, , 2012Chagnaud and Bass, 2014], robust or moderate label was identified in forebrain and midbrain sites that are major nodes in the central vocal and auditory networks ( Fig. 1 2000; Goodson and Bass, 2002;Bass et al, 2005;Kittelberger and Bass, 2013].…”
Section: Discussionmentioning
confidence: 99%
“…However, these authors also reported that motoneurons, which directly establish the firing rate of sonic muscles and vocal features, establish their connections with the sonic muscle prior to establishing connections with the premotor neurons in the hindbrain. More recently, Chagnaud and Bass (2014) showed that the central pattern generator (CPG) anatomy of two batrachoidids (P. notatus and Opsanus tau; subfamilies Batrachoidinae and Porichthinae, respectively) differs at the levels of both the pacemaker-motoneuron circuit and the afferent pre-pacemaker neurons and this may contribute to the species-specific patterning of frequency and amplitude-modulated vocalisations. Together, this suggests that the maturation of CPG and patterns of connectivity between hindbrain vocal nuclei may underline the vocal differentiation observed in the Lusitanian toadfish.…”
Section: Ontogenetic Vocal Differentiationmentioning
confidence: 99%